Middle school :my brother is a big fat liar - Patterson, James, 1947- (Little, Brown and Co., 2014)
When Rafe Kane enters middle school, he teams up with his best friend, "Leo the Silent," to create a game to make school more fun by trying to break every rule in the school's code of conduct.